مسح فيروس Y البطاطا وسلالاته في حقول إنتاج البطاطا في محافظة اللاذقية, سورية - اســماعيل عماد دأود; راعي ســليم يونس (Latakia University Journal -Biological Sciences Series, 2019)
هدفت هذه الدراسة إلى التحري عن فيروس واي البطاطا (PVY) وسلالاته في عينات نباتية جمعت من حقول البطاطا في اللاذقية-سورية من مواقع صنوبر جبلة, نهر العرب, الشراشير, البصة, بوقا. استخدم في الدراسة اختبار البصمة النسيجية المناعية المباشر (TBIA) والأجسام المضادة وحيدة الكلون لفيروس PVY وسلالاته PVYN, PVYC, PVYC/O. أشارت نتائج الاختبار إلى تباين نسب انتشار الفيروس PVY وسلالاته باختلاف المواقع المدروسة. بلغت نسبة العينات المصابة بالفيروس PVY 65.3% من العينات الكلية, وبلغت نسبة العينات التي تفاعلت مع الأجسام المضادة للسلالات 77.5%, في حين 24.5% من العينات لم تتفاعل مع أي من الأجسام المضادة للسلالات. كما تباينت نسبة السلالات الفيروسية في العينات المختبرة بحالة فردية (PVYN بنسبة 48.6%, PVYO بنسبة 35.1%) أو كإصابات مختلطة بسلالتين ولم يتم الكشف عن وجود إصابة مفردة بالسلالة PVYC. The aim of this study is to survey Potato virus Y (PVY) strains in potato production fields in Lattakia province, Syria; Sanaober Jablah, Naher Alarab, Sharasher, Bassah, and Bouka sites. Direct tissue blot immunobinding assay (TBIA) and monoclonal antibodies against PVY and PVY strains (PVYN, PVYC, PVYC/O) were used in this study. Results revealed differences in distribution rates of PVY and its strains among surveyed sites. About 65.33% of total tested samples were PVY infected, and 77.5% of these reacted positively with monoclonal antibodies against PVY strains, whereas 24.5 % reacted negatively. Single infection with one PVY strain has been detected in deferent rates, 48.6% for PVYN and 35.1% for PVYO. Mixed infection with PVY strains was also detected. Single infection with PVYC strain has not been found.